Study of Prevalent Maternal Beliefs Regarding Diet during Common Childhood Illness in Thar Desert, Rajasthan - Singh, Madhu B; Lakshminarayan, J (Annals of Arid Zone, 2016)
A study was conducted in 17 villages of Thar Desert, categorized in three ecological sub-regions, i.e., Marusthali, Shekhawati and Luni basin. Information on maternal beliefs regarding diet during common childhood illness, demography and other socio-economic aspects was collected through interview techniques from 434 rural young mothers who represented the entire caste groups present. Majority of the women (94%) were illiterate, and 48% belonged to lower and upper middle-income groups. The respondents opined on the basis of their traditional beliefs, items preferred and restricted during different types of illness. Accordingly the food items were divided into cold, hot, light, windy, heavy and other characteristics. Cold food like curd with rice and turmeric were preferred during diarrhoea and dysentery, but hot food like millet and jaggery were avoided. During measles and typnoid only hot food like lebta of millet was preferred to hasten the appearance of rashes. Information on such local maternal beliefs regarding diet during common childhood illness in Thar Desert will help in organizing nutrition and health education programs for desert areas by encouraging the useful practices and discouraging the harmful ones.